Natural Products for the Potential Use of Neuroprotective and Neurorestorative Effects in Stroke - Hansen Chen; Qingkun Liu (MDPI AG, 2023)
Stroke is the second leading cause of death and the third leading cause of disability worldwide, with limited treatment options [...]